The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/environments4010018
|View full text |Cite
|
Sign up to set email alerts
|

Sonication Effects on Atrazine Dissipation in Vadose Zone Sediment Slurries

Abstract: Herbicide atrazine easily leaches to groundwater, where it is persistent. We studied whether sonication accelerates atrazine dissipation (100 mg·L −1 ) in vadose zone sediment slurries. Sediments were from 11.3 to 14.6 m depths in an atrazine-contaminated groundwater area. The slurries and autoclave-sterilized slurries were sonicated (bath, 43 kHz, 320 W) for 0, 5, 10, 20, or 30 min once/twice a day, and atrazine concentrations were followed. Atrazine concentrations raised in the sterilized slurries sonicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In long-term (180 days) degradation experiments, using low atrazine concentrations of 20 µg L −1 in water circulating columns at a flow rate of 2 mL min −1 , atrazine dissipation rates have been estimated to be two to five times faster than in stagnant flasks [5], while pharmaceuticals dissipation was not enhanced at flow rates of 1.7-3.4 mL min −1 [65]. The short-term results of this study showed that at quite a high atrazine concentration below 10-18 mg L −1 , high flow rate (16.7 mL min −1 )-induced changes in the sediment columns did not improve atrazine dissipation, apparently due to the good colloid formation ability [21][22][23], while the amount adsorbed to the sediments was low (about 50.1 µg). The atrazine distribution coefficient K d , which is the ratio of atrazine adsorbed to that dissolved into the liquid phase, increases when the atrazine concentration decreases [66].…”
Section: Atrazine-contaminated Aquifer Sediments and Remediationmentioning
confidence: 51%
See 1 more Smart Citation
“…In long-term (180 days) degradation experiments, using low atrazine concentrations of 20 µg L −1 in water circulating columns at a flow rate of 2 mL min −1 , atrazine dissipation rates have been estimated to be two to five times faster than in stagnant flasks [5], while pharmaceuticals dissipation was not enhanced at flow rates of 1.7-3.4 mL min −1 [65]. The short-term results of this study showed that at quite a high atrazine concentration below 10-18 mg L −1 , high flow rate (16.7 mL min −1 )-induced changes in the sediment columns did not improve atrazine dissipation, apparently due to the good colloid formation ability [21][22][23], while the amount adsorbed to the sediments was low (about 50.1 µg). The atrazine distribution coefficient K d , which is the ratio of atrazine adsorbed to that dissolved into the liquid phase, increases when the atrazine concentration decreases [66].…”
Section: Atrazine-contaminated Aquifer Sediments and Remediationmentioning
confidence: 51%
“…The rapid increase in microbial numbers in the liquid phase of the atrazine-added sediment slurries, but not in the treatments without atrazine, indicates that some of the atrazine was degraded as a microbial growth substrate (Table 4). The subsurface sediments contaminated with about 13 µg kg −1 of atrazine [32] appeared to inherently contain microbes that are able to rapidly degrade atrazine, which is often disputed due to the absence of microbial pesticide degradation at concentrations below the water solubility limit of 33 mg L −1 [6,21,54].…”
Section: Microbial Growth In the Sediment-water Systemsmentioning
confidence: 99%